Private Sector and the 1% Disability Quota: Legal Responsibilities in Indonesia - Agustin, Dila Wahyu; Gunadi, Ariawan (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The background of this research is the challenge of fulfilling the 1% disability employment quota by private companies in Indonesia, in accordance with Law No. 8 of 2016 on Persons with Disabilities. Despite the regulations outlining this obligation, companies often face obstacles such as low legal awareness, social stigma, and a lack of disability-friendly infrastructure. This study employs a juridical-normative research method with statutory, conceptual, and analytical approaches to relevant regulations and their implementation practices. The findings show that although the government has made efforts to encourage companies to meet the disability quota through incentives and sanctions, consistent implementation remains limited. Strengthening oversight and increasing legal awareness are necessary to address these challenges. Additionally, applicable solutions include improving accessibility facilities and providing training programs for companies to better address the challenges of disability inclusion.